PENINGKATAN KETERAMPILAN SISWA MEMPRODUKSI TEKS ANEKDOT MENGGUNAKAN MEDIA KARIKATUR DAN PENDEKATAN SAINTIFIK - Warni, Setia (Universitas Tanjungpura, 2018)
This study purpose to describe the planning, implementation, and result of skills learning of producing anecdote text using caricature media and scientific approach to the students in the first grade of Vocational school I Mempawah Hilir in Accounting program in Akademic year 2016/2017. The data was used in this study was obtained from planning action, implementation, observation, and reflection on writing learning/produce a anecdote text written.. The conclusion of this study based on the result research is caricature media and scientific approach can improve the quality process, especially the attitude and the results of the students writing skills of anecdote text. It can be evidenced by the students attitude on the aspects of honesty, discipline, responsibility, manners, and responsive in I, II, and III cycle. The quality of skills produce student’s written increased, the first cycle of the average value of 62.76 with a 42% level of completeness. The second cycle the average value of 74.11 with a 61% level of completeness. Cycle III the average value of 86.78 with a 89% level of completeness.